Genomic investigation of a suspected Klebsiella pneumoniae outbreak in a neonatal care unit in sub-Saharan Africa. Issue 11 (18th November 2021) - Cornick, Jennifer; Musicha, Patrick; Peno, Chikondi; Seager, Ezgi; Iroh Tam, Pui-Ying; Bilima, Sithembile; Bennett, Aisleen; Kennedy, Neil; Feasey, Nicholas; Heinz, Eva; Cain, Amy K.
Abstract : A special-care neonatal unit from a large public hospital in Malawi was noted as having more frequent, difficult-to-treat infections, and a suspected outbreak of multi-drug-resistant Klebsiella pneumoniae was investigated using genomic characterisation. All K. pneumoniae bloodstream infections (BSIs) from patients in the neonatal ward ( n =62), and a subset of K. pneumoniae BSI isolates ( n =38) from other paediatric wards in the hospital, collected over a 4 year period were studied. After whole genome sequencing, the strain sequence types (STs), plasmid types, virulence and resistance genes were identified. One ST340 clone, part of clonal complex 258 (CC258) and an ST that drives hospital outbreaks worldwide, harbouring numerous resistance genes and plasmids, was implicated as the likely cause of the outbreak. This study contributes molecular information necessary for tracking and characterizing this important hospital pathogen in sub-Saharan Africa.